A laboratorial prototype of a weight measuring system using optical fiber Bragg grating sensors embedded in silicone rubber. (February 2015) - Vieira, J.C.; Morais, O.M.F.; Vasques, C.M.A.; de Oliveira, R.
Highlights: A laboratorial prototype of a weight measuring system was developed and calibrated. Optical fiber Bragg grating sensors embedded in a silicone rubber tray were used. The sensors presented linear response to weight variations between 0.5 and 500 g. Good repeatability and excellent sensibility were obtained in the experimental tests. Proof-of-concept was performed trough laboratory tests and finite element predictions. Abstract: Weight measurements in a laboratorial environment are often affected by external factors from different origins, such as mechanical, thermal or electromagnetic effects. In this paper an innovative solution of a laboratorial weight measuring system somewhat circumventing these limitations is developed recurring to optical fiber Bragg grating (FBG) sensors embedded in a silicone rubber tray. As a result of the coupling between the FBG sensors and the low stiffness host material, the wavelength shift of the FBG sensors increases when the rubber tray is subjected to a transversal load. This paper reports the results obtained during the development and calibration of a prototype system for technology proof-of-concept.